Place and Being: Higher Education as a Site for Creating Biskabii---Geographies of Indigenous Academic Identity - McAlpin, Jennifer Dawn (2008)
I use an Indigenous decolonizing process, as seen through a Dine and/or Anishinaabe lens. The approach can be understood in Dine and Anishinaabe terms as Hozho nahazdlii', Andaa Wenjigewin and Mino-Bimaadiziwin, respectively. These paradigms are related to auto-ethnographic and heuristic approaches to knowledge that center on the lived experiences of the researcher as the primary interpretive framework for analysis. Made available in DSpace on 2015-09-25T19:55:03Z (GMT). No. of bitstreams: 2 license.txt: 4848 bytes, checksum: 96035ab3f5e1c23cc7138a224ce498bd (MD5) 3314851.pdf: 3401266 bytes, checksum: ce64d90ed68ef50827617a31132cbe1a (MD5) Previous issue date: 2008 Embargo set by: Seth Robbins for item 81319 Lift date: Forever Reason: Restricted to the U of I community idenfinitely during batch ingest of legacy ETDs Restricted to the U of I community idenfinitely during batch ingest of legacy ETDs U of I Only 240 p. Thesis (Ph.D.)--University of Illinois at Urbana-Champaign, 2008.